The prognostic value of respiratory symptoms and performance status in ambulatory cancer patients and unsuspected pulmonary embolism; analysis of an international, prospective, observational cohort study. (16th September 2021) - Maraveyas, Anthony; Kraaijpoel, Noémie; Bozas, George; Huang, Chao; Mahé, Isabelle; Bertoletti, Laurent; Bartels‐Rutten, Annemarieke; Beyer‐Westendorf, Jan; Constans, Joel; Iosub, Diana; Couturaud, Francis; Muñoz, Andres J.; et al.
Abstract: Background: Optimal risk stratification of unsuspected pulmonary embolism (UPE) in ambulatory cancer patients (ACPs) remains unclear. Existing clinical predictive rules (CPRs) are derived from retrospective databases and have limitations. The UPE registry is a prospective international registry with pre‐specified characteristics of ACPs with a recent UPE. The aim of this study was to assess the utility of risk factors captured in the UPE registry in predicting proximate (30‐, 90‐ and 180‐day) mortality and how they performed when applied to an existing CPR. Objectives: To evaluate risk factors for proximate mortality, overall survival, recurrent venous thromboembolism and major bleeding, in the patients enrolled in the UPE registry cohort. Methods: Data from the 695 ACPs in this registry were subjected to multivariate logistic regression analyses to identify predictors independently associated with proximate mortality and overall survival. The most consistent predictors were applied to the Hull CPR, an existing 5‐point prediction rule. Results: The most consistent predictors of mortality were patient‐reported respiratory symptoms within 14 days before, and ECOG performance status at the time of UPE. These predictors applied to the Hull‐CPR produced a consistent correlation with proximate mortality and overall survival (area under the curve [AUC] = 0.70 [95% CI 0.63, 077], AUC = 0.65 [95% CI 0.60, 070], AUC = 0.64 [95% CI 0.59, 068], and AUC = 0.61, 95% CI 0.57, 0.65, respectively). Conclusion: In ACPs with UPE, ECOG performance status logged contemporaneously to the UPE diagnosis and respiratory symptoms prior to UPE diagnosis can stratify mortality risk. When applied to the HULL‐CPR these risk predictors confirmed the risk stratification clusters of low‐intermediate and high‐risk for proximate mortality as seen in the original derivation cohort.